2017
DOI: 10.3389/fpsyt.2017.00254
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cigarette Smoking and Nicotine Dependence in Men and Women Residing in Two Provinces in China

Abstract: AimsAlthough it is known that there is a high smoking prevalence among Chinese, key issues such as social and environmental factors impacting smoking initiation and persistence, the percentage of smokers considered nicotine dependence (ND), and the availability and use of ND treatments have rarely been investigated.MethodsTo address these issues, from 2012 to 2014, we conducted a large-scale study in the Zhejiang and Shanxi provinces of China using the Fagerström Test for Nicotine Dependence and other validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 43 publications
2
25
1
Order By: Relevance
“…The present study also revealed that most current smokers in the five studied ethnic groups initiate smoking as well as begin regular smoking during adolescence, a finding which accords with previous studies,18 19 indicating smoking is a serious problem for teenagers in rural southwest China. In addition, all four ethnic minorities studied had a lower age of smoking initiation and of regular smoking than the Han population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study also revealed that most current smokers in the five studied ethnic groups initiate smoking as well as begin regular smoking during adolescence, a finding which accords with previous studies,18 19 indicating smoking is a serious problem for teenagers in rural southwest China. In addition, all four ethnic minorities studied had a lower age of smoking initiation and of regular smoking than the Han population.…”
Section: Discussionsupporting
confidence: 92%
“…That males smoked significantly more and were more likely to have a nicotine addiction than females accords with other studies 21 22. However, the overall prevalence rate of current smoking and nicotine dependence among males was higher in the present study than in both previous Chinese studies as well as studies in other countries 18 23. The findings thus provide further evidence that smoking and nicotine dependence remains a widespread challenge for rural Chinese male adults, particularly in ethnic minority populations.…”
Section: Discussionsupporting
confidence: 69%
“…Due to extremely few female smokers in China, 25 we consecutively recruited 159 Han Chinese male subjects who had scheduled for surgery of anterior cruciate ligament reconstruction from 2014 to 2016, including 81 active smokers and 78 non-smokers. Sociodemographic data, including age and years of education, and clinical data such as the history of substance abuse and dependence were obtained according to self-report and confirmed by the next of kin and family members.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Cigarette smoking, a worldwide public health problem, is a major cause of death from lung and cardiovascular disease and cancer. (Benowitz, ) The prevalence of smoking is 66.1 and 3.2% for males and females, respectively, in China, perhaps the highest prevalence in the world owing to the low price of cigarettes and poor national education (Chaloupka, Sweanor, & Warner, ; Ma et al, ). Considering the large population in China, smoking is a big public health problem.…”
Section: Introductionmentioning
confidence: 99%